COST MINIMIZATION ANALYSIS OF ANTIHYPERTENSIVE DRUG USE IN CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS - Utami, Indah Kurnia; Rakanita, Yasinta; Dewi, Niluh Puspita (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Hypertension is the primary cause of Chronic Kidney Disease (CKD), as it damages blood vessels in the kidneys. The most commonly used management for hypertension as monotherapy includes Calcium Channel Blockers (CCB) such as Amlodipine and Angiotensin Receptor Blockers (ARB) such as candesartan. Patients with CKD undergoing hemodialysis depend on dialysis machines, which impacts their economic burden. Therefore, a cost analysis review of drugs with the same therapeutic goals is necessary. This was a non-experimental study with a descriptive design. Data were collected through retrospective purposive sampling from January to December 2023 using medical records and payment data for inpatient treatments with hemodialysis that met the inclusion criteria. Direct medical costs included antihypertensive, other medication, service and facility fees, and medical support costs. Of the 100 samples that met the inclusion criteria from January to December 2023, amlodipine was the most commonly used antihypertensive (56%), followed by candesartan (38%). The average direct medical costs were IDR 184.350 for Amlodipine and IDR 561,339 for candesartan. The patient characteristics by gender showed a higher percentage of males (52%) than of females (48%). By age, the majority were in the late adult group (67%), whereas the elderly accounted for (33%). The Amlodipine group achieved more significant cost minimization than the candesartan group. Future studies should examine the potential of amlodipine in reducing the economic burden of limited resources.  Keywords: antihypertensive, CMA, CKD